SERANGAN DAN KERUSAKAN TANAMAN CENGKEH YANG DISEBABKAN OLEH Hexamitodera semivelutina Hell. DI DESA RERER KABUPATEN MINAHASA - Runaweri, Christian; Pelealu, J.; Manueke, J. (EUGENIA, 2017)
ABSTRACT The aim of this research is to know the attack and damage of clove stem borer Hexamitodera semivelutina at some elevation in Rerer village of Kombi sub-district of Minahasa Regencyfor 2 months (February - April 2017). The research was conducted by survey  on farmers’ clove plantation area. The research was using a stratified random sampling method with observing the incidence and severity of H. semivelutina pest of clove plant. Treadment using 3 stratum height of place from sea level  that is 0 - <300 meters from sea level (mfsl), 300 - <600 (mfsl), and >600 (mfsl). The result of this research are the symptom of attack and damage of clove plant caused by H. Semivelutina pest as follows : incidence rate and severity according to altitude of place 0 - <300 mfsl are 24.67% and 12.55%, while at height 300 - <600 mfsl are 42.34% and 22.88 %, and at altitude> 600 mfsl are 61.67% and 33.66%.Keywords : incidence of pest, severity of pest, Hexamitodera semivelutina